Nanocomposites based on LbL films of polyaniline and sodium montmorillonite clay - Barros, Anerise de; Ferreira, Mariselma; Constantino, Carlos J. L. [UNESP]; Ferreira, Marystela (Elsevier B.V., 2014)
Layer-by-layer (LbL) films were fabricated with alternating layers of montmorillonite (Na+-MMT) and either polyaniline emeraldine salt (PAni-ES) or polyethyleneimine (PEI). Molecular-level interactions between the film components probed with FTIR and Raman spectroscopies led to distinct arrangements for the clay nanostructures. The electrostatic interaction between charged groups in PAni-ES and Na+-MMT caused aggregation with the polymer chains located around the clay sheets, while for the PEI/Na+-MMT LbL film the interlayer distance was increased owing to intercalation. The LbL films deposited onto ITO substrates were used as electrochemical sensors for detecting heavy metal ions simultaneously using electrochemical measurements by square wave anodic stripping voltammetry (SWAS). (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Layer-by-layer films; Sodium montmorillonite clay; Polyaniline; Electrochemical sensor; Detection of heavy metal ions